Dietary supplementation with citrus peel extract in transition period improves rumen microbial composition and ameliorates energy metabolism and lactation performance of dairy cows - Lingxue Ju; Qi Shao; Zhiyuan Fang; Erminio Trevisi; Meng Chen; Yuxiang Song; Wenwen Gao; Lin Lei; Xinwei Li; Guowen Liu; Xiliang Du (Journal of Animal Science and Biotechnology, 2024)
Abstract Background During the transition period, excessive negative energy balance (NEB) lead to metabolic disorders and reduced milk yield. Rumen microbes are responsible for resolving plant material and producing volatile fatty acids (VFA), which are the primary energy source for cows. In this study, we aimed to investigate the effect of citrus peel extract (CPE) supplementation on rumen microbiota composition, energy metabolism and milk performance of peripartum dairy cows. Methods Dairy cows were fed either a basal diet (CON group) or the same basal diet supplemented with CPE via intragastric administration (4 g/d, CPE group) for 6 weeks (3 weeks before and 3 weeks after calving; n = 15 per group). Samples of serum, milk, rumen fluid, adipose tissue, and liver were collected to assess the effects of CPE on rumen microbiota composition, rumen fermentation parameters, milk performance, and energy metabolic status of dairy cows. Results CPE supplementation led to an increase in milk yield, milk protein and lactose contents, and serum glucose levels, while reduced serum concentrations of non-esterified fatty acid, β-hydroxybutyric acid, insulin, aspartate aminotransferase, alanine aminotransferase, and haptoglobin during the first month of lactation. CPE supplementation also increased the content of ruminal VFA. Compared to the CON group, the abundance of Prevotellaceae, Methanobacteriaceae, Bacteroidales_RF16_group, and Selenomonadaceae was found increased, while the abundance of Oscillospiraceae, F082, Ruminococcaceae, Christensenellaceae, Muribaculaceae UCG-011, Saccharimonadaceae, Hungateiclostridiaceae, and Spirochaetaceae in the CPE group was found decreased. In adipose tissue, CPE supplementation decreased lipolysis, and inflammatory response, while increased insulin sensitivity. In the liver, CPE supplementation decreased lipid accumulation, increased insulin sensitivity, and upregulated expression of genes involved in gluconeogenesis. Conclusions Our findings suggest that CPE supplementation during the peripartum period altered rumen microbiota composition and increased ruminal VFA contents, which further improved NEB and lactation performance, alleviated lipolysis and inflammatory response in adipose tissue, reduced lipid accumulation and promoted gluconeogenesis in liver. Thus, CPE might contribute to improve energy metabolism and consequently lactation performance of dairy cows during the transition period.